An insect isoscape of UK and Ireland. (10th June 2021) - Newton, Jason
Abstract : Rationale: The study of insect migration is problematic due to the small size of insects. Stable isotope analysis can be used to elucidate movement, either by geographic assignment of location of a species, or by simply distinguishing migrant from resident populations. There are few isoscapes of any kind in the UK/Ireland available for interrogation. Thus, I have measured stable isotope ratios (of H, C, N and S) of 299 individuals of the non‐migratory Brimstone moth ( Opisthograptis luteolata ) collected from 93 locations around the UK and Ireland by citizen scientists. Methods: After removing lipids, stable isotope ratios were measured by continuous flow isotope ratio mass spectrometry, using either a conventional elemental analyser (C, N and S) or a high‐temperature, thermal conversion elemental analyser in reductive mode. Results: Maps (isoscapes) were constructed that illustrate the stable isotope spatial distribution of this insect. These are the first isoscapes of H, C, N and S of biological samples covering both UK and Ireland. Conclusions: The insect isoscape patterns can be explained from what we know of moth diet, climate and geology. Sulfur isotopes may be of particular use for distinguishing individuals from areas of unique geology. Isoscape patterns may (with care) predict isotope compositions of other, herbivorous, non‐aquatic, chitinous taxa. Such isoscapes, when extended beyond the UK and Ireland, would provide a useful tool to elucidate insect migration.